Presentation is loading. Please wait.

Presentation is loading. Please wait.

The lambda calculus David Walker CS 441. the (untyped) lambda calculus a language of functions e ::= x | \x.e | e1 e2 v ::= \x.e there are several different.

Similar presentations


Presentation on theme: "The lambda calculus David Walker CS 441. the (untyped) lambda calculus a language of functions e ::= x | \x.e | e1 e2 v ::= \x.e there are several different."— Presentation transcript:

1 the lambda calculus David Walker CS 441

2 the (untyped) lambda calculus a language of functions e ::= x | \x.e | e1 e2 v ::= \x.e there are several different ways to evaluate lambda calculus expressions so far, we’ve studied left-to-right, call-by-value: amazingly, despite it’s minimalism, the lambda calculus is Turing complete and may serve as a foundation for all computation e1 --> e1’ e1 e2 --> e1’ e2 e2 --> e2’ v e2 --> v e2’ (\x.e) v --> e [v/x] (b) (app1) (app2)

3 extending the lambda calculus lambda calculus with booleans: e ::= x | true | false | test | \x.e | e1 e2 v ::= true | false | test | \x.e test e1 e2 e3 --> test e1’ e2 e3 (test1) e1 --> e1’ test v1 e2 e3 --> test v1 e2’ e3 (test2) e2 --> e2’ test v1 v2 e3 --> test v1 v2 e3’ (test3) e3 --> e3’ test true v2 v3 --> v2 (test-true) test false v2 v3 --> v3 (test-false) + all the other lambda calculus rules

4 booleans: the translation from +boolean into pure : translate(true) = \t.\f. t translate(false) = \t.\f. f translate(test) = \x.\y.\z. x y z translate(x) = x translate(\x.e) = \x.(translate(e)) translate(e1 e2) = translate(e1) translate(e2) values in the source language always get translated into values in the target language source language target language

5 boolean translation example: translate(test true s1 s2) = (\x.\y.\z.x y z) (\x.\y.x) v1 v2 (where v1 = translate s1 and v2 = translate s2) e1 --> e1’ e1 e2 --> e1’ e2 e2 --> e2’ v e2 --> v e2’ (\x.e) v --> e [v/x] (b) (app1) (app2)

6 boolean translation example: translate(test true s1 s2) = (\x.\y.\z.x y z) (\x.\y.x) v1 v2 (where v1 = translate s1 and v2 = translate s2) in the source language we have: test true s1 s2 --> s1 e1 --> e1’ e1 e2 --> e1’ e2 e2 --> e2’ v e2 --> v e2’ (\x.e) v --> e [v/x] (b) (app1) (app2)

7 boolean translation example: translate(test true s1 s2) = (\x.\y.\z.x y z) (\x.\y.x) v1 v2 (where v1 = translate s1 and v2 = translate s2) in the source language we have: test true s1 s2 --> s1 so in the target we want: (\x.\y.\z.x y z) (\x.\y.x) v1 v2 --> v1 e1 --> e1’ e1 e2 --> e1’ e2 e2 --> e2’ v e2 --> v e2’ (\x.e) v --> e [v/x] (b) (app1) (app2)

8 boolean translation example: translate(test true s1 s2) = (\x.\y.\z.x y z) (\x.\y.x) v1 v2 (where v1 = translate s1 and v2 = translate s2) in the source language we have: test true s1 s2 --> s1 so in the target we want: (\x.\y.\z.x y z) (\x.\y.x) v1 v2 --> v1 e1 --> e1’ e1 e2 --> e1’ e2 e2 --> e2’ v e2 --> v e2’ (\x.e) v --> e [v/x] (b) (app1) (app2)

9 boolean translation Theorem (Translation Preserves Semantics): If s1 --> s2 (in the lambda calculus with booleans) then (translate(s1)) --> (translate(s2)) (in the pure lambda calc) e1 --> e1’ e1 e2 --> e1’ e2 e2 --> e2’ v e2 --> v e2’ (\x.e) v --> e [v/x] (b) (app1) (app2)

10 booleans (((\x.\y.\z.x y z) (\x.\y.x)) v1) v2 --> _____________ e1 --> e1’ e1 e2 --> e1’ e2 e2 --> e2’ v e2 --> v e2’ (\x.e) v --> e [v/x] (b) (app1) (app2)

11 booleans ((\x.\y.\z.x y z) (\x.\y.x)) v1) --> ___________ (((\x.\y.\z.x y z) (\x.\y.x)) v1) v2 --> _____________ v2 e1 --> e1’ e1 e2 --> e1’ e2 e2 --> e2’ v e2 --> v e2’ (\x.e) v --> e [v/x] (b) (app1) (app2) (app1) e1 e1’

12 booleans (\x.\y.\z.x y z) (\x.\y.x) --> ___________ (\x.\y.\z.x y z) (\x.\y.x)) v1 --> ___________ v1 (((\x.\y.\z.x y z) (\x.\y.x)) v1) v2 --> _____________ v2 e1 --> e1’ e1 e2 --> e1’ e2 e2 --> e2’ v e2 --> v e2’ (\x.e) v --> e [v/x] (b) (app1) (app2) (app1) (b)

13 booleans \x.\y.\z.x y z (\x.\y.x) --> \y.\z.x y z [\x.\y.x / x] ((\x.\y.\z.x y z) (\x.\y.x)) v1) --> v1 (((\x.\y.\z.x y z) (\x.\y.x)) v1) v2 --> v2 e1 --> e1’ e1 e2 --> e1’ e2 e2 --> e2’ v e2 --> v e2’ (\x.e) v --> e [v/x] (b) (app1) (app2) (app1) (b)

14 booleans \x.\y.\z.x y z (\x.\y.x) --> \y.\z.(\x.\y.x) y z ((\x.\y.\z.x y z) (\x.\y.x)) v1) --> v1 (((\x.\y.\z.x y z) (\x.\y.x)) v1) v2 --> v2 e1 --> e1’ e1 e2 --> e1’ e2 e2 --> e2’ v e2 --> v e2’ (\x.e) v --> e [v/x] (b) (app1) (app2) (app1) (b)

15 booleans \x.\y.\z.x y z (\x.\y.x) --> \y.\z.(\x.\y.x) y z ((\x.\y.\z.x y z) (\x.\y.x)) v1) --> (\y.\z.(\x.\y.x) y z) v1 (((\x.\y.\z.x y z) (\x.\y.x)) v1) v2 --> v2 e1 --> e1’ e1 e2 --> e1’ e2 e2 --> e2’ v e2 --> v e2’ (\x.e) v --> e [v/x] (b) (app1) (app2) (app1) (b)

16 booleans (\x.\y.\z.x y z) (\x.\y.x) --> \y.\z.(\x.\y.x) ((\x.\y.\z.x y z) (\x.\y.x)) v1) --> \y.\z.(\x.\y.x) v1 (((\x.\y.\z.x y z) (\x.\y.x)) v1) v2 --> \y.\z.(\x.\y.x) v1 v2 e1 --> e1’ e1 e2 --> e1’ e2 e2 --> e2’ v e2 --> v e2’ (\x.e) v --> e [v/x] (b) (app1) (app2) (app1) (b)

17 booleans translate(true) = \t.\f. t translate(false) = \t.\f. f translate(and) = \b.\c. b c (translate(false)) translate(x) =... translate(and true true) = (\b.\c. b c (\t.\f.f)) (\t.\f.t) (\t.\f.t)

18 booleans translate(true) = \t.\f. t translate(false) = \t.\f. f translate(and) = \b.\c. b c (translate(false)) translate(x) =... translate(and true true) = (\b.\c. b c (\t.\f.f)) (\t.\f.t) (\t.\f.t) ===> wow is that ever tough to read...

19 booleans tru = \t.\f. t fls = \t.\f. f a = \b.\c. b c fls translate(and true true) = a tru tru = (\b.\c. b c fls) tru tru target language expression (ie: a and tru are just meta-variables I’m using to abbreviate and make more readable the translated term)

20 booleans tru = \t.\f. t fls = \t.\f. f a = \b.\c. b c fls a tru tru = (\b.\c. b c fls) tru tru --> (\c.tru c fls) tru e1 --> e1’ e1 e2 --> e1’ e2 e2 --> e2’ v e2 --> v e2’ (\x.e) v --> e [v/x] (b) (app1) (app2)

21 booleans tru = \t.\f. t fls = \t.\f. f a = \b.\c. b c fls a tru tru = (\b.\c. b c fls) tru tru --> (\c.tru c fls) tru --> tru tru fls e1 --> e1’ e1 e2 --> e1’ e2 e2 --> e2’ v e2 --> v e2’ (\x.e) v --> e [v/x] (b) (app1) (app2)

22 booleans tru = \t.\f. t fls = \t.\f. f a = \b.\c. b c fls a tru tru = (\b.\c. b c fls) tru tru --> (\c.tru c fls) tru --> tru tru fls = (\t.\f. t) tru fls e1 --> e1’ e1 e2 --> e1’ e2 e2 --> e2’ v e2 --> v e2’ (\x.e) v --> e [v/x] (b) (app1) (app2)

23 booleans tru = \t.\f. t fls = \t.\f. f a = \b.\c. b c fls a tru tru = (\b.\c. b c fls) tru tru --> (\c.tru c fls) tru --> tru tru fls = (\t.\f. t) tru fls -->(\f. tru) fls e1 --> e1’ e1 e2 --> e1’ e2 e2 --> e2’ v e2 --> v e2’ (\x.e) v --> e [v/x] (b) (app1) (app2)

24 booleans tru = \t.\f. t fls = \t.\f. f a = \b.\c. b c fls a tru tru = (\b.\c. b c fls) tru tru --> (\c.tru c fls) tru --> tru tru fls = (\t.\f. t) tru fls -->(\f. tru) fls --> tru e1 --> e1’ e1 e2 --> e1’ e2 e2 --> e2’ v e2 --> v e2’ (\x.e) v --> e [v/x] (b) (app1) (app2)

25 if statements e ::= x | v | e1 e2 | if e1 then e2 else e3 v ::= \x.e | true | false e1 --> e1’ e1 e2 --> e1’ e2 e2 --> e2’ v e2 --> v e2’ (\x.e) v --> e [v/x] (b) (app1) (app2) if e1 then e2 else e3 --> if e1’ then e2 else e3 (if1) if true then e2 else e3 --> e2 (if2) e1 --> e1’ if false then e2 else e3 --> e3 (if3)

26 An Example loop = (\x.x x) (\x.x x) if (\x.x) true then \x.x else loop --> if true then \x.x else loop --> \x.x

27 booleans what is wrong with the following translation? translate true = tru translate false = fls translate (if e1 then e2 else e3) = test (translate e1) (translate e2) (translate e3) translate (\x.e) = \x.(translate e) translate (e1 e2) = (translate e1) (translate e2)

28 booleans what is wrong with the following translation? translate true = tru translate false = fls translate (if e1 then e2 else e3) = tst (translate e1) (translate e2) (translate e3) e2 and e3 will both be evaluated regardless of whether e1 is true or false -- the target program might not terminate in some cases when the source program would pure lambda terms: tru = \t.\f.t fls = \t.\f.f tst = \x.\y.\z. x y z

29 example translate (if (\x.x) true then \x.x else loop) = tst translate((\x.x) true) (translate(\x.x)) (translate(loop)) = tst ((\x.x) tru) (\x.x) (loop) = tst ((\x.x) tru) (\x.x) ((\x.x x) (\x.x x)) e1 --> e1’ e1 e2 --> e1’ e2 e2 --> e2’ v e2 --> v e2’ (\x.e) v --> e [v/x] (b) (app1) (app2)

30 example translate (if (\x.x) true then \x.x else loop) = tst translate((\x.x) true) (translate(\x.x)) (translate(loop)) = tst ((\x.x) tru) (\x.x) (loop) = tst ((\x.x) tru) (\x.x) ((\x.x x) (\x.x x)) tst ((\x.x) tru) (\x.x) ((\x.x x) (\x.x x)) --> tst tru (\x.x) ((\x.x x) (\x.x x)) e1 --> e1’ e1 e2 --> e1’ e2 e2 --> e2’ v e2 --> v e2’ (\x.e) v --> e [v/x] (b) (app1) (app2)

31 example translate (if (\x.x) true then \x.x else loop) = tst translate((\x.x) true) (translate(\x.x)) (translate(loop)) = tst ((\x.x) tru) (\x.x) (loop) = tst ((\x.x) tru) (\x.x) ((\x.x x) (\x.x x)) tst ((\x.x) tru) (\x.x) ((\x.x x) (\x.x x)) --> tst tru (\x.x) ((\x.x x) (\x.x x)) (((\x.\y.\z. x y z) tru) (\x.x)) ((\x.x x) (\x.x x)) --> e1 --> e1’ e1 e2 --> e1’ e2 e2 --> e2’ v e2 --> v e2’ (\x.e) v --> e [v/x] (b) (app1) (app2)

32 example translate (if (\x.x) true then \x.x else loop) = tst translate((\x.x) true) (translate(\x.x)) (translate(loop)) = tst ((\x.x) tru) (\x.x) (loop) = tst ((\x.x) tru) (\x.x) ((\x.x x) (\x.x x)) tst ((\x.x) tru) (\x.x) ((\x.x x) (\x.x x)) --> tst tru (\x.x) ((\x.x x) (\x.x x)) (((\x.\y.\z. x y z) tru) (\x.x)) ((\x.x x) (\x.x x)) --> ((\y.\z. tru y z) (\x.x)) ((\x.x x) (\x.x x)) --> e1 --> e1’ e1 e2 --> e1’ e2 e2 --> e2’ v e2 --> v e2’ (\x.e) v --> e [v/x] (b) (app1) (app2)

33 example translate (if (\x.x) true then \x.x else loop) = tst translate((\x.x) true) (translate(\x.x)) (translate(loop)) = tst ((\x.x) tru) (\x.x) (loop) = tst ((\x.x) tru) (\x.x) ((\x.x x) (\x.x x)) tst ((\x.x) tru) (\x.x) ((\x.x x) (\x.x x)) --> test tru (\x.x) ((\x.x x) (\x.x x)) (((\x.\y.\z. x y z) tru) (\x.x)) ((\x.x x) (\x.x x)) --> ((\y.\z. tru y z) (\x.x)) ((\x.x x) (\x.x x)) --> (( \z. tru (\x.x) z) ) ((\x.x x) (\x.x x)) --> e1 --> e1’ e1 e2 --> e1’ e2 e2 --> e2’ v e2 --> v e2’ (\x.e) v --> e [v/x] (b) (app1) (app2)

34 example translate (if (\x.x) true then \x.x else loop) = tst translate((\x.x) true) (translate(\x.x)) (translate(loop)) = tst ((\x.x) tru) (\x.x) (loop) = tst ((\x.x) tru) (\x.x) ((\x.x x) (\x.x x)) tst ((\x.x) tru) (\x.x) ((\x.x x) (\x.x x)) --> tst tru (\x.x) ((\x.x x) (\x.x x)) (((\x.\y.\z. x y z) tru) (\x.x)) ((\x.x x) (\x.x x)) --> ((\y.\z. tru y z) (\x.x)) ((\x.x x) (\x.x x)) --> (( \z. tru (\x.x) z) ) ((\x.x x) (\x.x x)) --> e1 --> e1’ e1 e2 --> e1’ e2 e2 --> e2’ v e2 --> v e2’ (\x.e) v --> e [v/x] (b) (app1) (app2)

35 example translate (if (\x.x) true then \x.x else loop) = tst translate((\x.x) true) (translate(\x.x)) (translate(loop)) = tst ((\x.x) tru) (\x.x) (loop) = tst ((\x.x) tru) (\x.x) ((\x.x x) (\x.x x)) tst ((\x.x) tru) (\x.x) ((\x.x x) (\x.x x)) --> tst tru (\x.x) ((\x.x x) (\x.x x)) (((\x.\y.\z. x y z) tru) (\x.x)) ((\x.x x) (\x.x x)) --> ((\y.\z. tru y z) (\x.x)) ((\x.x x) (\x.x x)) --> (( \z. tru (\x.x) z) ) ((\x.x x) (\x.x x)) --> (( \z. tru (\x.x) z) ) ((\x.x x) (\x.x x)) -->... e1 --> e1’ e1 e2 --> e1’ e2 e2 --> e2’ v e2 --> v e2’ (\x.e) v --> e [v/x] (b) (app1) (app2)

36 booleans we saw this translation didn’t work: translate (if e1 then e2 else e3) = tst (translate e1) (translate e2) (translate e3) we need to delay execution of e2, e3 until the right time: translate (true) = \x.\y.(x (\x.x)) translate (false) = \x.\y.(y (\x.x)) translate (if e1 then e2 else e3) = (\x.\y.\z. x y z) (translate e1) (\w.translate e2) (\w.translate e3)... other cases...

37 pairs would like to encode the operations –create e1 e2 –fst p –sec p pairs will be functions –when the function is used in the fst or sec operation it should reveal its first or second component respectively

38 pairs create = \x.\y.\b. b x y fst = \p. p tru tru = \x.\y.x sec = \p. p fls fls = \x.\y.y

39 pairs create = \x.\y.\b. b x y fst = \p. p tru tru = \x.\y.x sec = \p. p fls fls = \x.\y.y fst (create tru fls) = fst ((\x.\y.\b. b x y) tru fls)

40 pairs create = \x.\y.\b. b x y fst = \p. p tru tru = \x.\y.x sec = \p. p fls fls = \x.\y.y fst (create tru fls) = fst ((\x.\y.\b. b x y) tru fls) -->* fst (\b. b tru fls)

41 pairs create = \x.\y.\b. b x y fst = \p. p tru tru = \x.\y.x sec = \p. p fls fls = \x.\y.y fst (create tru fls) = fst ((\x.\y.\b. b x y) tru fls) -->* fst (\b. b tru fls) = (\p.p tru) (\b. b tru fls)

42 pairs create = \x.\y.\b. b x y fst = \p. p tru tru = \x.\y.x sec = \p. p fls fls = \x.\y.y fst (create tru fls) = fst ((\x.\y.\b. b x y) tru fls) -->* fst (\b. b tru fls) = (\p.p tru) (\b. b tru fls) --> (\b. b tru fls) tru

43 pairs create = \x.\y.\b. b x y fst = \p. p tru tru = \x.\y.x sec = \p. p fls fls = \x.\y.y fst (create tru fls) = fst ((\x.\y.\b. b x y) tru fls) -->* fst (\b. b tru fls) = (\p.p tru) (\b. b tru fls) --> (\b. b tru fls) tru --> tru tru fls = (\x.\y.x) tru fls --> (\y.tru) fls --> tru

44 and we can go on... numbers arithmetic expressions (+, -, *,...) lists, trees and datatypes exceptions, loops, the general trick: –values will be functions – construct these functions so that they return the appropriate information when called by an operation


Download ppt "The lambda calculus David Walker CS 441. the (untyped) lambda calculus a language of functions e ::= x | \x.e | e1 e2 v ::= \x.e there are several different."

Similar presentations


Ads by Google